Insulin dynamics in young women with polycystic ovary syndrome and normal glucose tolerance across categories of body mass index. - Melania Manco; Lidia Castagneto-Gissey; Eugenio Arrighi; Annamaria Carnicelli; Claudia Brufani; Rosa Luciano; Geltrude Mingrone (PLoS ONE, 2014)
Background Evidence favours insulin resistance and compensatory hyperinsulinemia as the predominant, perhaps primary, defects in polycystic ovary syndrome (PCOS). The aim of the present study was to evaluate insulin metabolism in young women with PCOS but normal glucose tolerance as compared with age, body mass index and insulin resistance-matched controls to answer the question whether women with PCOS hypersecrete insulin in comparison to appropriately insulin resistance-matched controls. Research design and methods Sixty-nine cases were divided according to their body mass index (BMI) in normal-weight (N = 29), overweight (N = 24) and obese patients (N = 16). Controls were 479 healthy women (age 16-49 y). Whole body Insulin Sensitivity (WBISI), fasting, and total insulin secretion were estimated following an oral glucose tolerance test (C-peptide deconvolution method). Results Across classes of BMI, PCOS patients had greater insulin resistance than matched controls (p<0.0001 for all the comparisons), but they showed higher fasting and total insulin secretion than their age, BMI and insulin resistance-matched peers (p<0.0001 for all the comparisons). Conclusion Women with PCOS show higher insulin resistance but also larger insulin secretion to maintain normal glucose homeostasis than age-, BMI- and insulin resistance-matched controls.